2016
DOI: 10.1186/s12889-016-3784-4
|View full text |Cite
|
Sign up to set email alerts
|

The Brazilian comprehensive response to hepatitis C: from strategic thinking to access to interferon-free therapy

Abstract: BackgroundHepatitis C affects over 185 million people around the world. This silent disease is responsible for up to 700,000 deaths per year. Despite the scientific revolution in diagnosis and treatment, hepatitis C control remains a huge challenge due to the cost of effective medications.In response to the global outcry of hepatitis epidemic and the need to improve the nation’s public health response, the Ministry of Health of Brazil revolutionized hepatitis C treatment by incorporating highly effective drugs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
32
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 9 publications
0
32
0
2
Order By: Relevance
“…A strategic plan has been outlined recently to address HCV infection in Brazil. It comprises incorporating new, effective, affordable drugs guiding physicians in treating HCV patients, and promoting diagnostic campaigns in populations aged > 40 years, as recent studies have shown a higher prevalence of infection [8,12,13]. Studies assessing HCV prevalence in Brazil are scarce, and the HCV seroprevalence is estimated between 0.69 to 1.89% [6,13,14].…”
mentioning
confidence: 99%
“…A strategic plan has been outlined recently to address HCV infection in Brazil. It comprises incorporating new, effective, affordable drugs guiding physicians in treating HCV patients, and promoting diagnostic campaigns in populations aged > 40 years, as recent studies have shown a higher prevalence of infection [8,12,13]. Studies assessing HCV prevalence in Brazil are scarce, and the HCV seroprevalence is estimated between 0.69 to 1.89% [6,13,14].…”
mentioning
confidence: 99%
“…Globally, nine of the 10 people living with viral hepatitis are unaware of their infection, and lack of public knowledge is often compounded by viral hepatitis‐related stigma and discrimination. Implementation of a viral hepatitis strategy should therefore include awareness‐raising activities to generate demand for viral hepatitis care (eg through social media campaigns, such as in Brazil) in conjunction with supportive laws, policy and guidelines that aim to reduce stigma and enable the establishment of community‐focused responses …”
Section: Introductionmentioning
confidence: 99%
“…The initial hepatocellular lesion caused by hepatitis C virus, when not diagnosed and treated properly, progresses to liver fibrosis, cirrhosis, and even liver cancer. 3 Between 1992 and 2002, more than 1500 patients were treated at the outpatient clinic of the Fundação Santa Casa de Misericórdia do Pará (FSCMPA), 85% of whom were considered to have chronic liver disease. 1 Its chronic form presents a worldwide prevalence of around 3%, with more than 200 million infected, being 20-30% of these evolving to cirrhosis and 1-4% to hepatocellular carcinoma.…”
Section: Introductionmentioning
confidence: 99%
“…2 In Brazil, there are approximately 1.7 million hepatitis C carriers. 3 Between 1992 and 2002, more than 1500 patients were treated at the outpatient clinic of the Fundação Santa Casa de Misericórdia do Pará (FSCMPA), 85% of whom were considered to have chronic liver disease. 4 Liver biopsy is considered the gold standard in evaluating the degree of fibrosis when chronic liver disease is suspected.…”
Section: Introductionmentioning
confidence: 99%